(untitled) (Research, Society and Development, 2022)
The “phototherapeutic methods” constitute a very interdisciplinary and applied area, which is associated to several fundamental and applied sciences. Phototherapy techniques have been increasingly used in several areas of health, such as medicine, dentistry and veterinary medicine. “Photobiomodulation”, “Laser therapy”, “Low-level laser therapy” (LLLT) or “Low-level light therapy” (LLLT) consist in different names that are recognized some of these phototherapeutic procedures. Varying the type of light source, including lasers, LEDs, white polychromatic light, between others, these procedures have originated excellent results to decrease the pain and to increase the process of the healing process, including postoperative care, among other applications. Unlike Photodynamic Therapy (PDT), which is widely applied in cases of cancer and infectious diseases, between others, in phototherapy techniques, such as “photobiomodulation”, exogenous photosensitizers or photosensitizing (PS) agents are not added. Therefore, the “photobiomodulation” makes use of a kind of activation of endogenous chemical species, including chromophore groups and/or dyes present in the target biological tissue. The general characteristics of this type of phototherapy technique are analyzed and the future perspectives of expanding this type of application in veterinary medicine are very promising, both in terms of therapeutic efficacy and the low cost of the respective devices and procedures.